Disparities in health related quality of life among Illinoisans diagnosed with depressive disorder: findings from the 2017 BRFSS - Kathryn Mazurek; James Ciesla; Rexford Akakpo (BMC, 2020)
Abstract Background The United States experienced severe mental health budget cuts in many states across the nation during the years of the largest recession since the Great Depression. Illinois had one of the hardest hit mental health budgets in the country. The massive mental health funding cuts in Illinois, combined with the state's budget impasse, left fewer facilities available to provide treatment and support to those in need. Many of Illinois's most vulnerable populations either had reduced access, or no access to care. Serious spillover effects were felt by emergency rooms, community hospitals, and the criminal justice system. Therefore, the purpose of this research is to examine disparities in Health Related Quality of Life for those with depression after the funding cuts in Illinois. Methods Data from the 2017 Behavior Risk Factor Surveillance System was analyzed by using multivariate logistic regression models of the Health Related Quality of Life measures for Illinoisans diagnosed with depressive disorders. Results According to the regression models in this study, disparities exist in HRQOL for Illinoisans with depressive disorders. In all of the HRQOL models, income was associated with a reduction in HRQOL. Additionally, disparities exist in HRQOL for certain age groups and those who are unemployed. Interestingly, the models did not show any racial disparities as anticipated. Conclusion Without the basic policy-level deficiencies addressed, disparities in Health Related Quality of Life for Illinois's most vulnerable populations will continue to exist as will costly economic spillover effects.